2010
DOI: 10.1159/000312696
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and Phenotype of Patients with Gonadotropin-Releasing Hormone Receptor Mutations

Abstract: Human mutations in the gonadotropin releasing hormone receptor (GNRHR) gene cause autosomal recessive, normosmic idiopathic hypogonadotropic hypogonadism (IHH). At least 19 different mutations have been identified in this G-protein coupled receptor, which consist mostly of missense mutations. The Gln106Arg and Arg262Gln mutations comprise nearly half of the identified alleles. Most mutations impair ligand binding and all compromise cell signaling events. Some of the mutations also adversely affect activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…In addition, the study by Maione reported an absence of radioiodinated GnRH signal in p.Thr269Met transfected COS‐7 cells compared to wild‐type GnRHR. Subsequent to 1997, several cases of normosmic CHH associated with GNRHR mutations have been reported …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the study by Maione reported an absence of radioiodinated GnRH signal in p.Thr269Met transfected COS‐7 cells compared to wild‐type GnRHR. Subsequent to 1997, several cases of normosmic CHH associated with GNRHR mutations have been reported …”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to 1997, several cases of normosmic CHH associated with GNRHR mutations have been reported. 25,26 The GNRHR gene is located on the long arm of chromosome 4 (4q13.2) and consists of 3-exon gene spanning 18.7 kb that encodes a 328 amino acid protein. Inactivating mutations in GNRHR have been described in CHH patients with an autosomal recessive inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…These three mutations are founder mutations, suggesting a hypothetical selective advantage for heterozygote carriers (Choi et al ., ). The Gln106Arg and Arg262Gln mutations account for approximately half of all reported mutant alleles (Kim et al ., ). In case of compound heterozygosity, one allele frequently carries either Gln106Arg or Arg262Gln.…”
Section: Introductionmentioning
confidence: 97%
“…This variant appears most of the time in compound heterozygosity. However, three unrelated patients, two males and one female, have been reported to be homozygous for Q106R (14). All three patients display a mild phenotype, with a partial sexual development and for two of them, a spontaneous reversal of HH was reported.…”
Section: Resultsmentioning
confidence: 99%